FAMILY DYNAMICS AND LEARNING MINDSET IN A UNIVERSITY IN CAPIZ - Borres, Kim Rose Bacanto; Siglos, Caressa Lyn Aman; Ciudadano, Emmylou Demeties (President University, 2025)
Aspects of culture like family dynamics and student learning mindset are interrelated and have a significant impact on how people develop and, consequently, how our communities and countries develop in the future. This study aimed to determine the level of family dynamics and degree of learning mindset of three hundred thirty (330) first year students at Capiz State University-Pilar Satellite College for academic year 2023-2024, selected through stratified random sampling. A validated and reliable researcher-made questionnaire was used to gather the needed data. The statistical tools used to analyze and interpret the data were frequency count, percentage, mean, grand mean, t-test, analysis of variance and Pearson r. Results of the study revealed that the level of family dynamics in terms of emotional dynamics and conflict resolution were high. The degree of learning mindset in terms of growth mindset and fixed mindset were also high. There was a significant difference on the level of family dynamics when the respondents were grouped according to course. On the degree of learning mindset, there was a significant difference when the respondents were grouped according to course and family structure. There was no significant relationship between the level of family dynamics and the degree of learning mindset. The findings recommend that universities should improve student communication and support networks through workshops, conflict resolution training, emotional intelligence programs, and open feedback mechanism. Tailored interventions and resilience training are recommended for fixed mindset students, while growth mindset students are encouraged to continuously improve through criticism and feedback.